2014
DOI: 10.1155/2014/625905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron/Folic Acid Supplementation on the Outcome of Malaria Episodes Treated with Sulfadoxine-Pyrimethamine

Abstract: Folic acid supplementation may potentially alter the efficacy of sulfadoxine-pyrimethamine (SP) treatment in children with malaria. However, there is lack of evidence from randomized controlled trials and effects of folic acid supplementation on clinical efficacy of SP therapy remain moderately understood among children. In a double masked, placebo-controlled trial among preschool children in Pemba Island (Tanzania), iron and folic acid supplementation (Fe/FA) showed an increased risk of hospitalizations and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…At the level of the organism, ferritin protects the host during active infection, limiting the availability of iron to pathogens (26)(27)(28). In fact, oral iron supplementation during infection increases mortality in humans (29) and hypoferremia and elevated serum ferritin is common in human populations exposed to high pathogen loads (30). These laboratory abnormalities can be induced experimentally in mice by injection of IL-1α or TNF-α (31), cytokines with known effects on macrophage iron uptake, storage and recirculation.…”
Section: Heavy Chain Ferritin During Inflammationmentioning
confidence: 99%
“…At the level of the organism, ferritin protects the host during active infection, limiting the availability of iron to pathogens (26)(27)(28). In fact, oral iron supplementation during infection increases mortality in humans (29) and hypoferremia and elevated serum ferritin is common in human populations exposed to high pathogen loads (30). These laboratory abnormalities can be induced experimentally in mice by injection of IL-1α or TNF-α (31), cytokines with known effects on macrophage iron uptake, storage and recirculation.…”
Section: Heavy Chain Ferritin During Inflammationmentioning
confidence: 99%
“…53,54 Also, iron supplements taken during infection increase the chances of mortality in human beings. 55 Elevated level of ferritin in the blood causes hypoferremia-like condition in patients who are exposed to very high pathogens. 56 Experimental studies performed in mice show effects on macrophages, uptake of iron, and recirculation and storage when they are injected with cytokines, interleukin IL-1α, or TNF-α.…”
Section: Inflammation and Hyperferritinemiamentioning
confidence: 99%
“…The association between iron deficiency and malaria incidence is still controversial. Some studies have shown that iron supplementation may increase the risk of malaria incidence [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%